High-energy neutrinos from FR0 radio galaxies?. Issue 4 (31st January 2018) - Tavecchio, F; Righi, C; Capetti, A; Grandi, P; Ghisellini, G
Abstract: The sources responsible for the emission of high-energy (≳100 TeV) neutrinos detected by IceCube are still unknown. Among the possible candidates, active galactic nuclei with relativistic jets are often examined, since the outflowing plasma seems to offer the ideal environment to accelerate the required parent high-energy cosmic rays. The non-detection of single-point sources or – almost equivalently – the absence, in the IceCube events, of multiplets originating from the same sky position – constrains the cosmic density and the neutrino output of these sources, pointing to a numerous population of faint sources. Here we explore the possibility that FR0 radio galaxies, the population of compact sources recently identified in large radio and optical surveys and representing the bulk of radio-loud AGN population, can represent suitable candidates for neutrino emission. Modelling the spectral energy distribution of an FR0 radio galaxy recently associated with a γ-ray source detected by the Large Area Telescope onboard Fermi, we derive the physical parameters of its jet, in particular the power carried by it. We consider the possible mechanisms of neutrino production, concluding that p γ reactions in the jet between protons and ambient radiation is too inefficient to sustain the required output. We propose an alternative scenario, in which protons, accelerated in the jet, escape from it and diffuse in the host galaxy, producing neutrinos as a result of pp scattering with the interstellar gas, in strict analogy with the processes taking place in star-forming galaxies.